HPV vaccination coverage: slightly improved two‐dose schedule completion estimates and historical estimates lower on AIR than HPV Register. (31st March 2022) - Brotherton, Julia; Hendry, Alexandra; Dey, Aditi; Hull, Brynley P.; Beard, Frank
Abstract: Objective : To compare Australian Immunisation Register (AIR) human papillomavirus (HPV) vaccination coverage against historical data from the former National HPV Vaccination Program Register and estimate two‐dose vaccination coverage. Methods : Cross‐sectional analysis of registry data for adolescent birth cohorts (1998‐2007). Denominator populations were Medicare enrolments (AIR) and ABS estimated resident populations (HPV register). Results : For adolescents aged <17 years, AIR coverage estimates were several percentage points lower than HPV register estimates due to a larger Medicare enrolment denominator. Completed course coverage (two or three valid doses) for 15‐year‐old females in 2020 was 81.5% and for males 78.6%, higher than completed course coverage in 15‐year‐olds in 2019 (79.7 and 76.8% respectively). First dose coverage was similar for Indigenous adolescents but course completion was lower, although improving over time. Course completion was slightly lower (3.5‐5.7%) in areas of lowest socioeconomic status and greatest remoteness. Conclusions : Coverage is slightly lower using AIR than HPV register estimates. Moving from three to two doses has slightly improved completion, likely due to the wider dose spacing, but equity gaps remain. Implications for public health : An ongoing focus on equity in vaccine delivery is needed. Systems, reminders and catch‐up opportunities to ensure course completion remain important.